Pengaruh Electronik Word Of Mouth Dan Brand Image Terhadap Keputusan Pembelian Moisturizer Bioaqua Pada Platfrom Shopee Di Jakarta Utara - Anissa Sabilla; Sukirno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research is motivated by the high number of internet users in Indonesia, encouraging theskincare company Bioaqua to conduct its beauty business online to increase purchase decisions. Inearly 2024, Bioaqua planned a new strategy to stay competitive by increasing positive reviews on theShopee e-commerce platform and strengthening its brand image. However, Bioaqua's sales havenot yet met the expected target and still lag behind competitors. This study aims to analyze theinfluence of Electronic Word of Mouth (e-WOM) and Brand Image on purchase decisions. Theresearch uses a quantitative method with a questionnaire as the data collection tool, involving 133respondents. The results show that (1) Electronic Word of Mouth (e-WOM) has a significant influenceon purchase decisions, and (2) Brand Image also has a significant influence on purchase decisions,with a contribution value of 68.7%.Keywords: Electronic Word of Mouth, Brand Image, Purchase Decision